Reconstruction Of Authority Dispute Arrangements Judging In The Environment Of Judicial Power - Yulianto, Winasis; Silvana Amalia, Dyah (CV. Inara, 2024)
Reconstruction of Dispute Arrangements for the Authority to Judge in the Sphere of Judicial Authority is research to reconstruct the arrangement of disputes over the authority to judge within the jurisdiction of the judiciary from 1945 to the present. The objective to be achieved in this research is to find legal politics for the formation of laws regarding judicial disputes within the jurisdiction of the judiciary. The research method used in this research is normative juridical research, by examining various laws and regulations in accordance with the research problem. The research results show that disputes over the authority to judge within the judiciary are in the Supreme Court.